DEVELOPING ORAL SPEECH SKILLS OF HIGH SCHOOL STUDENTS BASED ON A COGNITIVE APPROACH (USING ENGLISH AS AN EXAMPLE) - Anora Nasimovna Ismailova, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Developing oral speech skills in high school students is a fundamental aspect of language education, especially in a global context where English serves as a key medium for communication, academia, and business. This discussion will explore reasons and strategies for improving high school students’ spoken English skills from a cognitive viewpoint.